Toxicologia de formulações comerciais de inseticidas para as abelhas Scaptotrigona aff. depilis e Apis mellifera L. - Gurgel, Leonardo dos Santos (2020)
Pesticides are considered responsible for the death of managed and wild bees. Despite some studies carried out with the active ingredients, little has been investigated about the action of commercial formulations, even though there are indications that inert materials potentiate the toxic effect of insecticides to bees. The present work aimed to investigate the toxicity to bees of three commercial products widely used in Brazil as pesticides; Verismo® (metaflumizone) and Actara® (thiametoxam) in Apis mellifera, and Evidence® (imidacloprid) in Scaptotrigona aff. depilis. The studies were conducted at the Bee Laboratory of the Zootechnics Department of the Federal University of Ceará between the years 2016 and 2018 and based on the international protocols of the OECD (Organization for Economic Cooperation and Development). The toxicity of insecticides was assessed by different exposure routes, using the Topical Average Lethal Dose (LD50) and the Average Lethal Concentration per ingestion (LC50) for A. mellifera and the Average Lethal Time (LT50), topical and oral for Scaptotrigona aff. depilis. Mortality data were recorded after 1, 6, 12, 24 and 48 hours for Apis and for 300 hours with intervals of 1, 6, 12 and 24 hours on the first day and from the second every 24 hours, for Scaptotrigona, from insect exposure different dosages of insecticides. For Apis the data were analyzed using a log-logistic model or Gompertz model with the help of the “drc” package present in the R statistical environment and for Scaptotrigona, the data were subjected to dose-response statistical analysis using the program Bioestat® - version 5.3. Actara® produced the topical LD50 of 0.055 (24h) and 0.052 (48h) ng c.p./µL/bee and the ingestion LC50 was 1.467 (24h) and 0.095 (48h) ng c.p./µL diet. Verismo® had a topical LD50 of 97.223 (24h) and 1.157 (48h) nL c.p./µL/bee and the ingestion LC50 was 2.493 (24h) and 0.334 (48h) nL c.p./µL diet. The LT50 topical Evidence® for Scaptotrigona aff. depilis was 22.1h and 29.4h if swallowed. The results showed that Actara® is much more toxic to A. mellifera than Verismo®, regardless of the route of exposure. Evidence® has been shown to be toxic to bees Scaptorigona aff. depilis, however, the lethal effect of the product manifests itself more quickly when contamination occurs topically than when orally.